Pain Management Barriers in Critical Care Units: A Qualitative study - Batiha, Abdul-Monim Mohammad (International Journal of Advanced Nursing Studies, 2013)
Background: Uncontrolled pain in intensive care units triggers physical and emotional stress responses, inhibits healing, increases the risk of other complications, and increases the length of ICU stay. Aim: To explore pain management barriers as identified by Jordanian critical care units. Method: This study employed qualitative content analysis with 37 participant nurses from Jordanian critical care units. Data were obtained through semi-structured serial interviews. Purpose nonprobability sampling was used for the initial interviews. Results: Several themes emerged to describe barriers to managing pain identified by the critical care nurses. These were grouped into three main themes: (1) Barriers related to patients with subgroups such as patient did not want to bother nurses, patients’ difficulty with completing pain scales, patients’ reluctance to take pain medications because of side-effects, patients reporting their pain to the doctor, but not to the nurse, and fatalistic beliefs. (2) Barriers related to nurses that included patient sedation, frequent complaints from patients, inconsistent practices around administering if necessary medications, time limitations, limited communication, the fear of side effects of pain drugs, physicians' lack of trust in the nursing assessment of pain in critically ill patients, inadequate staff knowledge of pain management, and fear of causing delirium or confusion. and (3) Barriers related to hospital policies includes: policies and rules of hospital, lack proper pain assessment tool, nursing shortages, powerlessness ,interruptions of activities relating to pain, lack of psychosocial support services, lack of alternatives nonpharmacologic therapy , and lack of pain management drugs. Conclusion: The results identify potential pain management barriers which can be considered when developing and disseminating policies and procedures in managing the pain in Jordanian critical care settings.